Validating the Voice of the Crowd During Disasters - Estuar, Ma. Regina Justina E (Archīum Ateneo, 2016)
Since the late 1990 s, the intensity of tropical cyclones have increased over time, causing massive flooding and landslides in thePhilippines. Nationwide Operational Assessment of Hazards or Project NOAH was put in place as a responsive program for disaster prevention and mitigation. Part of the solution was to set up nababaha.com(www.nababaha.com) and FloodPatrol which provided the public with a web and mobile phone based application for reporting flood height. This paper addresses the problem of providing an interactive and visual method of validating crowdsourced flood reports for the purpose of helping frontline responders and decision makers in disaster management. The approach involves finding the neighborhood of the crowdsourced flood report and weather station data based on their geospatial proximity and time record. A report is classified as correct if it falls within the obtained confidence interval of the crowdsourced flood report neighborhood. The neighborhood of crowdsourced flood reports are correlated with weather station data, which serves as the ground truth in the validation process. Use cases are presented to provide examples of automatic validation. The results of this study is beneficial to disaster management coordinators, first-line responders, government unit officials and citizens. The system provides an interactive approach in validating reports from the crowd, aside from providing an avenue to report flood events in an area. Overall, this contributes to the study of how crowdsourced reports are verified and validated.